Thyroid fibrous band and levator glandulae thyroideae muscle: two different structures associated with the pyramidal lobe of the thyroid gland - Milojević, Bojan; Živaljević, Vladan; Paunović, Ivan; Maliković, Aleksandar (Archives of Biological Sciences, 2021)
Paper description: This study was performed to resolve the dilemma about the origin and structure of the fibrous or muscular band found in close association with the pyramidal lobe of the thyroid gland. The investigation was performed using microdissection and histological examination in 106 human post-mortem The thyroid fibrous band and levator glandulae thyroideae are defined herein as two different structures of the thyroid gland. The thyroid fibrous band may be considered as the partial fibrous remnant of the thyroglossal duct while levator glandulae thyroideae may be treated as infrahyoid or laryngeal muscle. Abstract: We investigated two structures that are in close association with the pyramidal lobe of the thyroid gland. Our investigation was performed using microdissection and histological examination in 106 human postmortem specimens. The first investigated structure was identified as the thyroid fibrous band that was present in 28.3% of cases. This band was always associated with the pyramidal lobe (which was significantly longer and thicker when associated with this band) and it had a constant hyo-pyramidal extension; it was located close to the midsagittal plane and predominantly composed of dense irregular connective tissue. The second investigated structure was the levator glandulae thyroideae muscle, which was associated with the pyramidal lobe in only 13.6% of cases. This muscle had a double extension, hyo-pyramidal and laryngo-pyramidal, located farther from the midsagittal plane, it was longer and thinner than the thyroid fibrous band and predominantly composed of striated muscle fibers. We confirmed our hypothesis that the thyroid fibrous band, which may be considered as the partial fibrous remnant of the thyroglossal duct and levator glandulae thyroideae, and which may be considered as infrahyoid or laryngeal muscle, are two different structures of the thyroid gland.